PARAMETERS OF INTERACTION BETWEEN THE STRATEGIC ACCOUNTING SYSTEM AND STRATEGIC MANAGEMENT - Savchenko, Alla; Storozhuk, Dmytro (Український економічний часопис, 2024)
The efficiency of enterprises depends on the correct and timely assessment of past events, the current state, and the determination of strategy. The adaptation of an enterprise's internal capabilities to external threats is carried out through strategic management, which relies on accounting and analytical support. The lack of consensus on the relationship between strategic management and accounting gives rise to various options and does not allow the construction of a unified concept for the further development of accounting within the strategic management system. The analysis of possible options for the correlation between strategic management and accounting has shown that businesses can independently determine ways of interaction and build a unified system for the strategic development of the enterprise within their own policies.